Adaptive Control of Weld Penetration and Trajectory for Robotic GTAW - Sadeghi, Mir Bahram H. (1996)
A statistical-adaptive control method for weld bead penetration and joint following in Tungsten Inert Gas Welding as an approach to process control of robotic GTAW has been designed and the sections related to joint following and prediction of the bead width as well as penetration depth were simulated. Weld process parameters such as base current and time, pulse current and time, electrode tip to workpiece distance, filler traveling speed, torch speed and workpiece thickness were used for finding the equations which describe the interrelationship between the aforementioned variables and penetration depth as well as bead width. These equations were developed from the statistical regression analysis of 80 welds deposited using various combinations of welding parameters. For monitoring of workpiece thickness variations, an ultrasonic device was used. In order to accurately control the weld trajectory, a CCD camera was used. The results showed that the misalignment of the progressive heat affected zone which is adjacent to the weld puddle can be detected and used for control of the weld trajectory. Also, it was found that scanning of a certain region of the captured image in front of the weld puddle decreases the data processing time drastically. In continuation of this work, a cascade control system for control of welding velocity as well as an algorithm for off·line generation and control of weld 3-D trajectory was developed.